Modeling Hadith-Based Ethical Values and Student Behavior in Indonesian Islamic Higher Education - Asy'ari, Emha Hasan Ayatullah; Muthalib, Abd; Sumarni, Sumarni; Khairunnisa, Ashma; Hasya, Muhammad Fadhlan Azka (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2026)
Hadith plays a central role as a primary source of Islamic ethical guidance; however, its transformation from textual knowledge into observable behavior remains theoretically fragmented and empirically underexplored in contemporary research. This study examines how the internalization of hadith-based ethical values influences student behavior, with Islamic family values serving as a mediating mechanism and the institutional learning environment acting as a moderating factor. Using a quantitative survey design, data were collected from 228 undergraduate students enrolled in Islamic education-related programs and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that the internalization of hadith values significantly affects student behavior both directly and indirectly through Islamic family values, demonstrating partial mediation. The institutional learning environment also exerts a significant direct influence and plays a compensatory moderating role by reducing dependence on individual levels of ethical internalization in shaping value orientation. These findings suggest that hadith should be understood not merely as a textual source but as a living ethical system operating across individual, familial, and institutional dimensions. This study contributes to contemporary hadith studies and Islamic education by offering an empirical model of how prophetic teachings are internalized and translated into behavior within modern educational settings.